Optimasi Penjadwalan Asisten Praktikum pada Laboratorium Pembelajaran Menggunakan Algoritme Genetika (Studi Kasus : Fakultas Ilmu Komputer Universitas Brawijaya) - Nadia Natasa Tresia Sitorus; Imam Cholissodin; Budi Darma Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Scheduling is an important thing to be prepared carefully for the sake of an activity doing well.Good and effective scheduling will make the activities work and be well organized. Practicumis a routine activity for the application of materials that have been accepted by students.Practicum can work well if the teaching schedule of the practicum assistant does not collidewith the lecture schedule or their other activities. Genetic algorithm is one of algorithm thatcan complete the teaching schedule of practicum assistant through computation process. Thedata in conducting the research is the data from practicum schedule, practicum assistant andthe schedule of the assistant's willingness. The code of the practicum assistant is representedon the chromosome using the permutation method. The sequence of genes on thechromosomes represents the code of the practicum schedule. The crossover method appliedis one-cut-point, with mutation method using reciprocal exchange, and elitsm selectionmethod. The test result obtained optimal genetic algorithm parameter with total population5000, generation 500, with cr and mr value is 0,9 and 0,1. The output of the system is theteaching schedule of the laboratory teaching assistant.